Fluorospectroscopy of Dye-Loaded Liposomes in Photonic Crystal Fibers - Yong, Derrick (2016)
The immobilization and probing of liposomes within photonic crystal fibers was demonstrated for the first time. A bioactive surface was used to tether the liposomes. This bioactive surface consisted of streptavidin bound to a photochemically functionalized biotin layer. Bound streptavidin, hence, enabled the further binding of biotinylated dye-loaded liposomes. In-fiber fluorescence spectroscopy was used to quantify the streptavidin coverage density. The same method was also used to characterize the surface-tethered liposomes. The further observation of a unique phenomenon-photobleaching dequenching-was used for the first time as an indication of liposomal content retention. This indicated no rupturing of liposomes, highlighting them as bioderived analogues to dye-doped nanoparticles. The demonstrated integration of liposomes with optical waveguides shows potential as a biointegrated photonic device.